Influence of Weather Variables on the Sorghum Yield - Pande, Vyas; Gupta, B R.D (Annals of Arid Zone, 2016)
A modified form of Fisher’s technique has been applied to examine the influence of distribution of weather variables on sorghum yield throughout its life cycle in Surat district, Gujarat. The multiple regression analysis based on 36 years of data (1950-1985) indicated that the weather variables rainfall, maximum and minimum temperatures, relative humidity, and duration of sunshine influence the sorghum yield significantly. The results revealed that the sorghum responds differently to weather variables curing different stages of its development. The yield estimates obtained based on the weather variables are discussed.